Case Report: Renal artery stenosis in children: ultrasound as a decisive diagnostic and therapy-accompanying technique! - Brasseler, Maire; Finkelberg, Ilja; Müntjes, Carsten; Cetiner, Metin (Frontiers in Pediatrics, 2023)
Introduction: Renal artery stenosis in children is rare, the recommended diagnostic algorithm is controversial in pediatric cohorts including catheter based angiography, CT angiography, magnetic resonance angiography and ultrasound. Case presentation: We report a case of an 11-year-old girl with renal artery stenosis in whom ultrasonography played a decisive role confirming the diagnosis and accompanying therapeutic percutaneous transluminal renal artery angioplasty. Conclusion: Improved ultrasound techniques including examiner experience contribute to the improvement of renal artery stenosis diagnosis in children. In particular localized sensitive blood flow velocity analysis displays its advantages compared to other imaging modalities in this case. Therefore, ultrasound should play an important role in future study designs addressing the search for the best diagnostic algorithm. Summary: The advantages of ultrasound technique in pediatric patients with renal artery stenosis compared to other imaging modalities are highlighted.